2021
DOI: 10.1111/jipb.13169
|View full text |Cite
|
Sign up to set email alerts
|

Combined analyses of translatome and transcriptome in Arabidopsis reveal new players responding to magnesium deficiency

Abstract: Translational control of gene expression, including recruitment of ribosomes to messenger RNA (mRNA), is particularly important during the response to stress. Purification of ribosome‐associated mRNAs using translating ribosome affinity purification (TRAP) followed by RNA‐sequencing facilitates the study of mRNAs undergoing active transcription and better proxies the translatome, or protein response, to stimuli. To identify plant responses to Magnesium (Mg) deficiency at the translational level, we combined tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…This enzyme plays a crucial role in the regulation of chlorophyll production, which is essential for photosynthesis and plant growth. In our study, the expression of CHLM only occurred in MgD (T1) and low Mg supply (T2) (Figure 6), suggesting that MGD or very low supply affected the expression of the key enzymatic gene [6]. Dysfunction of CHLM can lead to impaired chlorophyll synthesis and affect the overall development and growth of plants [35].…”
Section: Mg Imbalances Affect Mulberry Plant Growth By Changing Chlor...mentioning
confidence: 64%
See 1 more Smart Citation
“…This enzyme plays a crucial role in the regulation of chlorophyll production, which is essential for photosynthesis and plant growth. In our study, the expression of CHLM only occurred in MgD (T1) and low Mg supply (T2) (Figure 6), suggesting that MGD or very low supply affected the expression of the key enzymatic gene [6]. Dysfunction of CHLM can lead to impaired chlorophyll synthesis and affect the overall development and growth of plants [35].…”
Section: Mg Imbalances Affect Mulberry Plant Growth By Changing Chlor...mentioning
confidence: 64%
“…Mg plays a critical role in a broad range of enzymatic activities, including nucleotide metabolism and the cycle of nucleic acids in transcription, splicing, or replication, as part of its essential function in plant growth and development [4]. It is the core atom in the chlorophyll molecules of photosynthesizing organisms and a co-factor necessary to activate more than 300 enzymes [6,7]. Even though Mg is crucial for plant development and growth, it receives less attention than other macronutrients such as N, P, and K, consequently giving it the name "the forgotten element" [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is also interesting to note that temperature, together with light, is a network of signaling mechanisms that regulate plant growth and development, typically PhyB can be used as a thermal sensor to control temperature response (Casal and Balasubramanian 2019 ). Both Fe and Mg play indispensable roles in plant Chl metabolism (Li et al 2021 ; Nam et al 2021 ; Liu et al 2023b ). We believe that BCM1, which has only recently been revealed, appears to be closely related to Mg 2+ (Zhang et al 2020 ), but the upstream transcription factors on which it relies are not yet conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Transcript levels of the gene encoding Chl a / b -binding protein 2 (CAB2) were downregulated within just 3 days after Mg deficiency was induced (Ogura et al 2020 ). Comparative analysis of transcriptional and translational differences under early Mg deficiency revealed that mutants of the transcription factor HY5, H+/CATION EXCHANGER 1 and 3 (CAX1 and CAX3), and UBIQUITIN 11 (UBQ11) exhibited an earlier onset of yellowing phenotype under Mg deficiency (Li et al 2021 ).The cbd1 mutant exhibited reduced Chl content and lower Mg levels in the thylakoid compared to the wild type. Additionally, both cbd1 and cbd1gun5 mutants showed an accumulation of Mg-Proto IX.…”
Section: Metal Ions: Stress On Chlorophyll Metabolism By Deficiencies...mentioning
confidence: 99%
“…Concerning N relative change, some of the top 50 SNPs were linked to ASN1 (AT3G47340), which is an actor of N status and remobilization 17,18 . The H+/CATION EXCHANGER 1 (CAX1) gene (AT2G38170), involved in the response to Mn deficiency, was also linked to SNPs associated with Mn content under elevated CO2 19 . Some of the top 50 SNPs identified for Fe relative change were linked to MCO2 (AT5G21100) and MCO3 (AT5G21105) genes, which have been recently characterized as actors of the regulation of Fe homeostasis 20 .…”
Section: Genetic Architecture Of the Ionome Response To Elevated Co2 ...mentioning
confidence: 99%